1997
DOI: 10.1002/(sici)1096-911x(199703)28:3<213::aid-mpo12>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Successful management with interferon alpha-2a after prednisone therapy failure in an infant with a giant cavernous hemangioma

Abstract: A giant cavernous hemangioma of the left arm with severe thrombocytopenia and consumptive coagulopathy was observed in a neonate. Initial treatment with prednisone, platelet transfusions, and clotting replacement failed to control the bleedings. The child was then treated with daily subcutaneous infusions of interferon alpha‐2a. Coagulopathy rapidly improved and transfusions were drastically reduced. The hemangioma regressed progressively and disappeared after 4 months of treatment. Med. Pediatr. Oncol. 28:213… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…To date, many factors known to promote or inhibit angiogenesis have been identified, including growth factors, cytokines and proteases [27]. Previous studies showed that IFN-α has anti-angiogenic properties in various tumors such as Kaposi's sarcomas [28], infantile hemangiomas [29] and some vascular-rich malignancies, melanoma, renal cell carcinoma and neuroendocrine tumors [30]. Therefore, we focused in the present study on the anti-angiogenic effects of the combination of IFN-α and 5-FU to determine the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many factors known to promote or inhibit angiogenesis have been identified, including growth factors, cytokines and proteases [27]. Previous studies showed that IFN-α has anti-angiogenic properties in various tumors such as Kaposi's sarcomas [28], infantile hemangiomas [29] and some vascular-rich malignancies, melanoma, renal cell carcinoma and neuroendocrine tumors [30]. Therefore, we focused in the present study on the anti-angiogenic effects of the combination of IFN-α and 5-FU to determine the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…IFN therapy has been clinically evaluated as the treatment of melanoma (136, 137), renal cell carcinoma (138, 139), myeloproliferative disorders (140, 141), lymphomas (142), neuroendocrine tumors (143) as well as vascular neoplasias including pulmonary hemangiomatosis (144), infantile hemangiomas (145), Kaposi’s sarcoma (146), and malignant hemangiopericytomas (147). …”
Section: Clinical Aspects Of Type I Ifn-mediated Polarization Of Neutmentioning
confidence: 99%
“…In cases associated with TAs, therapies directed at tumor destruction have been numerous and, unfortunately, associated with unpredictable results. Reported pharmacologic therapies, used either alone or in combination with other treatments, include corticosteroids, interferon‐alpha, vincristine, and cyclophosphamide . Procedural therapies have included surgical excision ± grafting, pulsed‐dye laser, radiation, arterial embolization, and pneumatic compression .…”
Section: Discussionmentioning
confidence: 99%